2003
DOI: 10.1364/ao.42.002436
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of fluorophore concentration in tissue-simulating media by fluorescence measurements with a single optical fiber

Abstract: Quantifying fluorescent compounds in turbid media such as tissue is made difficult by the effects of multiple scattering and absorption of the excitation and emission light. The approach that we used was to measure fluorescence using a single 200-microm optical fiber as both the illumination source and the detector. Fluorescence of aluminum phthalocyanine tetrasulfonate (AlPcS4) was measured over a wide range of fluorophore concentrations and optical properties in tissue-simulating phantoms. A root-mean-square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 19 publications
0
63
0
Order By: Relevance
“…Diffusion models of light propagation have demonstrated average RMSE between 5% and 25% when measuring fluorescence from tissue-mimicking phantoms, and a similar 1-D formulation demonstrated less than 10% RMSE when assessing fluorescence from epithelial and stromal tissues within the human cervix. 29,31,32,44 A limitation of these approaches is the reliance on a priori knowledge of the optical properties of the tissues being studied. The attenuation of whole blood can be measured prior to an imaging procedure, but the optical properties of the vessel wall cannot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion models of light propagation have demonstrated average RMSE between 5% and 25% when measuring fluorescence from tissue-mimicking phantoms, and a similar 1-D formulation demonstrated less than 10% RMSE when assessing fluorescence from epithelial and stromal tissues within the human cervix. 29,31,32,44 A limitation of these approaches is the reliance on a priori knowledge of the optical properties of the tissues being studied. The attenuation of whole blood can be measured prior to an imaging procedure, but the optical properties of the vessel wall cannot.…”
Section: Discussionmentioning
confidence: 99%
“…After calibration to known fluorophore concentrations in tissue-mimicking phantoms, estimated values of μ a;f;x · Φ can be used to determine the concentration of unknown fluorescent samples. 32 …”
Section: Analytical Light Propagation Model and Fluorescence Estimationmentioning
confidence: 99%
“…The use of multiple optical-fibres ensured a good signal to noise ratio was obtained. Diamond et al (2003b) extended the work by establishing a calibration curve to allow fluorophore concentrations to be quantified. For wavelengths in the red to near infrared region, fluorophore concentrations were recovered from tissue phantoms with an r.m.s.…”
Section: Measurement-methods Based Techniquesmentioning
confidence: 99%
“…Recent in vivo studies have shown large variation of photosensitizer concentration in different tissue types, thus suggesting determination of this quantity in vivo in the region of treatment directly [22,58]. To include the drug concentration in the evaluation of PDT dose, in situ fluorescence [59] or absorption [39,[60][61][62][63] measurements of photosensitizer can be made interstitially using optical fibers. Absorption spectroscopy has the advantage that, in addition to drug concentration, tissue hemodynamics can be monitored, which is important because tissue oxygenation is known to affect PDT efficacy in vitro [36,64].…”
Section: Quantification Of Drug Concentration and Tissue Oxygenationmentioning
confidence: 99%